Effects of Dendropanax morbiferus Leaf Extract on Sleep Parameters in Invertebrate and Vertebrate Models - Kayoung Ko; Yejin Ahn; Ga Yeong Cheon; Hyung Joo Suh; Yun Jae Cho; Sung-Soo Park; Ki-Bae Hong (MDPI AG, 2023)
Dendropanax morbiferus is highly valued in traditional medicine and has been used to alleviate the symptoms of numerous diseases owing to its excellent antioxidant activity. This study aimed to evaluate the sleep promotion and related signaling pathways of D. morbiferus extract (DE) via behavioral analysis, molecular biological techniques, and electrophysiological measurements in invertebrate and vertebrate models. In Drosophila, the group treated with 4% DE experienced decreased subjective nighttime movement and sleep bout and increased total sleeping time. Moreover, substantial changes in locomotor activity, including distance moved, velocity, and movement, were confirmed in the 4% DE-treated group. Compared to Drosophila in which insomnia and oxidative stress were induced by exposure to 0.1% caffeine, the DE-treated group improved sleep-related parameters to the level of the normal group. In the Drosophila model, exposure to 4% DE upregulated the expression of gamma-aminobutyric acid (GABA)-related receptors and serotonin receptor (5-HT1A), along with the expression of antioxidant-related factors, glutathione, and catalase. In the pentobarbital-induced sleep test using ICR mice, the duration of sleep was markedly increased by high concentration of DE. In addition, through the electroencephalography analysis of SD-rats, a significant increase in non-rapid-eye-movement sleep and delta waves was confirmed with high concentrations of DE administration. The increase in sleep time and improvement in sleep quality were confirmed to be related to the expression of altered GABA receptors and the enhancement of the contents of the neurotransmitters GABA and serotonin (5-HT) because of high DE administration. High-dose administration of DE also increased the expression of antioxidant-related factors in the brain and significantly decreased malondialdehyde content. Taken together, DE induced improvements in sleep quantity and quality by regulating neurotransmitter content and related receptor expression, along with high antioxidant activity, and may have a therapeutic effect on sleep disorders.